Comparison of Emerson and Hafiz Based on Claudio Guillen's Comparative Literary Theory of Influence - Saber Noie (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
The poetry of Khajeh Mohammad Hafiz Shirazi has vastly influenced the poetry of Ralph Waldo Emerson, as many critics have noted but have not demonstrated. Emerson is an American poet whose work reflects the influences of Persian poets, among which that of Hafiz is remarkable. The influence of Hafiz on Emerson includes memorable images, themes and motifs. While one can argue that this influence was indirect, it is obvious from the closeness of certain similarities, from Emerson’s intimate knowledge of Hafiz’s poetry, and from his love for Persian poetry, that the influence was more direct than otherwise. Although Emerson knew German and read Hafiz in German translations yet, he embarked on translating the poems of Hafiz in English in order to master Hafiz’s poetry and to introduce him to American readers. These translations themselves are another proof of the claim of influence of Hafiz on Emerson. The methodology of this article is to set the poems of the two poets over against one another and study them watchfully in order to demonstrate the influence of the precursor poet on the belated poet. Therefore the sources of familiarity of Emerson with Hafiz must not be forgotten and should be brought to the surface.